Investigation on the soil corrosivity towards the buried water supply pipelines in Kamerotar town planning area of Bhaktapur, Nepal - Dhakal, Yub Raj; Dahal, Kumar P; Bhattarai, Jagadeesh (BIBECHANA, 2013)
Soil parameters such as moisture content, pH, resistivity, oxidation-reduction potential, chloride and sulfate ions can give an indication of the soil corrosivity towards the buried-galvanized steels and cast-iron pipelines used to supply the drinking water in Nepal. Present research work was focused to examine such soil parameters collected from Kamerotar town planning area of Bhaktapur district of Nepal. Concentrations of these soil parameters measured in this study are found as: moisture content (18-77%), pH (3.0-9.3), resistivity (11600-71400 ohm.cm), oxidation-reduction potential (87-426 mV vs SHE), chloride (28-135 ppm) and sulfate (20-226 ppm). These soil parameters gave an indication of “moderately corrosive” to “mildly corrosive” behavior of soils on the buried-galvanized steels and cast-iron pipelines used in the study area. It was found a good correlation between the soil resistivity and moisture content as well as the chloride content in soils. The soil resistivity was generally decreased with increasing both the moisture and chloride contents in soils. DOI: http://dx.doi.org/10.3126/bibechana.v10i0.8454 BIBECHANA 10 (2014) 82-91